2018
DOI: 10.1002/aur.1940
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in plasma cytokine levels in chinese children with autism spectrum disorder

Abstract: Alteration of immune system function is an important risk factor for autism spectrum disorder (ASD). Here we found that the levels of cytokines, including Eotaxin, TGF-β1 and TNF-α, are elevated in Chinese children with ASD, as compared to typically developing children. The change in TGF-β1 level was most prominent in boys, while that of Eotaxin was more significant in girls. These results provide evidence for changes in cytokine profile in Chinese children with ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 48 publications
0
25
1
1
Order By: Relevance
“…Plasma cytokine levels have been shown to be altered in 87 Chinese ASD children (2–6 years old). In this study, eotaxin, TGF-b and TNF-α were up-regulated while no differences were observed in IL-8 levels between ASD (assessed using the Autism Diagnostic Observation Schedule, second edition, ADOS-2) and 41 normally developing age-matched control children [ 19 ]. Interestingly, in this study, most of the recruited ASD children were between the moderate and severe end of the ADOS-2 scale.…”
Section: Inflammatory Conditions In Autism Spectrum Disordersmentioning
confidence: 99%
“…Plasma cytokine levels have been shown to be altered in 87 Chinese ASD children (2–6 years old). In this study, eotaxin, TGF-b and TNF-α were up-regulated while no differences were observed in IL-8 levels between ASD (assessed using the Autism Diagnostic Observation Schedule, second edition, ADOS-2) and 41 normally developing age-matched control children [ 19 ]. Interestingly, in this study, most of the recruited ASD children were between the moderate and severe end of the ADOS-2 scale.…”
Section: Inflammatory Conditions In Autism Spectrum Disordersmentioning
confidence: 99%
“…Several lines of evidence point to ongoing and prominent activation of innate myeloid immune cells in ASD (Ashwood et al, 2011;Enstrom et al, 2010;Hu et al, 2018;Inga Jácome et al, 2016;Molloy et al, 2006). Furthermore, we and others have shown increased activation of circulating myeloid cells in the periphery following ex vivo stimulation, including changes in gene expression and the release of pro-inflammatory cytokines (Ashwood et al, 2011;Enstrom et al, 2010;Mendizabal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that TNFα levels are increased in serum of individuals with ASD when compared to controls ( 21 , 23 , 25 , 26 , 34 36 ); however, studies on plasma have provided conflicting results ( 4 , 28 , 35 ). These discordant results may reflect the matrix used as well as methodological issues, including different assessment instruments, and clinical and demographic characteristics of ASD populations studied.…”
Section: Discussionmentioning
confidence: 99%